Simple Isolation of Cordycepin from Cordyceps militaris by Dual-Normal Phase Column Chromatography and Its Potential for Making Kombucha Functional Products - Nguyen Van Quan; Yu Iuchi; La Hoang Anh; Mehedi Hasan; Tran Dang Xuan (Separations, 2022)
Cordycepin (3′-deoxyadenosine) is a potent bioactive metabolite of the medicinal fungus Cordyceps militaris, which has been increasingly exploited to treat various chronic diseases in humans. However, the current synthesis and purification procedures of cordycepin are principally laborious and complicated. This study provides a simple protocol approach to isolate and purify cordycepin from C. militaris by normal phase column chromatography at room temperature. Besides, this is the first to investigate the potential of cordycepin and cordycepin-included extracts from C. militaris for making Kombucha functional products. By a repeated column chromatography, an amount of 1.16 g of cordycepin is isolated from 2.8 kg of fruiting bodies of C. militaris, which obtained an efficiency of 83.26% compared to that estimated by high-performance liquid chromatography (HPLC). The purity of cordycepin is confirmed by thin-layer chromatography (TLC), HPLC, and proton nuclear magnetic resonance (1H NMR). In addition, kombucha-fermented extracts from cordycepin and cordycepin-included fractions show potential biological activities in terms of antioxidant, anti-diabetes via α-glucosidase inhibitory assay, and cytotoxicity via MTT assay on Meg-01 and HL-60 cell lines. Further studies on optimization of extraction protocol and verification of health benefits of kombucha products from cordycepin should be conducted prior to the official mass production.